The Influence of Digital Marketing and Service Quality on Consumer Preferences for Coffee Shops in Malang City - Prasetio Utomo; Fatasya Aulya Ngindana Zulfa; Fitriyah; Barianto Nurasri Sudarmawan (Pustaka Peradaban, 2023)
The coffee shop industry has experienced heightened competitiveness, propelled by the consistent growth in coffee consumption and production. Evolving beyond mere purveyors of coffee, these establishments have become significant social hubs, especially among student communities. This study aims to explore the impact of digital marketing and service quality on consumer preferences within the coffee shop landscape in Kota Malang, Indonesia.. The evaluation of service quality employs the